SELF EFFICACY OF ADOLESCENT AVOID FREE SEX THROUGH FAMILY INVOLVEMENT AND PEER GROUP INTERACTION - Sang Ayu Made Adyani; Putri Zalfa (Jurnal Keperawatan Respati Yogyakarta, 2023)
Adolescent experience various kinds of changes, including experiencing sexual maturity which encourages them to engage in risky sexual behaviour. Self-efficacy for adolecents can help them in preventing and avoiding free sex. The research design use a quantitative through cross sectional analytical descriptive approach. The population in this study were high school students with a sample of 223 respondents. The results of the chi square statistical test obtained p = 0.000. It can be concluded that there is a relationship between family involvement and self-efficacy away from free sex; and there is a relationship between peer interaction with self-efficacy away from free sex. Teenagers are expected to increase self-efficacy to stay away from free sex behavior and can choose positive groups in interacting.